Nature humaine ou acte de volonté ? Le péché originel de l’agent éthique chez s. Anselme - Trego, Kristell (Revue d'études augustiniennes et patristiques, 2007)
How shall we understand that Adam can be at the origin of an original sin? How this sin can be a sin if we did not commit it, but inherited it, by nature? Such questions are obviously theological, but their treatment is philosophical. The solution brought by Anselm to the problem of the original sin in his De incarnatione Verbi et de peccato originali depends thus in a remarkable way on the ethical reflections of the three moral dialogues of the years 1080-1085. It is the recognition of the will at the origin of the acts which helps him to solve some of the difficulties raised by this concept: the original sin indicates the fact that we are born such as we will sin when we’ll have a (rational) will. If Augustine had understood the original sin as being a (second) nature, Anselm insists on the voluntary acts, in order to be able to hear the term “sin” stricto sensu as signifying a personal sin that each one will commit, and not simply a sin made by another than us (Adam). But, if the ethical agent sins then well voluntarily and thus freely, the exercise of this freedom depends on the state in which we are born. By his freedom, man excludes himself from the natural course of the things, but can only do what he received to be able to do.